Avoiding bias in parasite excretion estimates: the effect of sampling time and type of faeces - Villanua, D; Perez-Rodriguez, L; Gortazar, C; Hoefle, U; Vinuela, J (Parasitology, 2006)
The study of host-parasite relationships usually requires reliable estimates of parasite intensity, which is often estimated from parasite propagule concentration in faeces. However, parasite excretion in faeces may be subject to variation due to endogenous or exogenous factors that must be identified to obtain reliable results. We analysed the effect of the hour of sample collection on propagule counts of 2 intestinal parasites infecting the red-legged partridge: the capillarid nematode Aonchoteca caudinflata and coccidia of the genus Eimeria (Protozoa). Also, we test whether there are differences in propagule counts between caecal and intestinal faeces. Individual faecal samples from infected birds were collected daily at 4 different hours during several days. The hour of the day exerted a very strong effect on propagule counts, excretion of both types of parasites showing a clear and constant increase from dawn to dusk. Also, capillarid eggs were more abundant in intestinal than in caecal faeces, whereas the inverse pattern was found for coccidian oocysts. Standardization of the hour of sample collection or statistical control of this variable is recommendable to prevent bias. Similarly, in bird species with long caeca, consistent collection of one type of faeces may avoid significant errors in parasite burden estimates.